2015
DOI: 10.1120/jacmp.v16i3.5247
|View full text |Cite
|
Sign up to set email alerts
|

Use of 3D printers to create a patient‐specific 3D bolus for external beam therapy

Abstract: The purpose of this paper is to demonstrate that an inexpensive 3D printer can be used to manufacture patient‐specific bolus for external beam therapy, and to show we can accurately model this printed bolus in our treatment planning system for accurate treatment delivery. Percent depth‐dose measurements and tissue maximum ratios were used to determine the characteristics of the printing materials, acrylonitrile butadiene styrene and polylactic acid, as bolus material with physical density of 1.04 and 1.2 g/cm3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
124
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(130 citation statements)
references
References 17 publications
4
124
0
2
Order By: Relevance
“…Made to order metal 3D printed devices (Hsu and Ellington 2015), 3D printed models for surgical planning (Pietrabissa et al 2015; Scawn et al 2015), and 3D printed tools (Burleson et al 2015) highlight some of the current and future biomedical applications of conventional 3D printing technologies. Bioprinting techniques have also been applied to bone tissue engineering.…”
Section: Applications Of Bioprintingmentioning
confidence: 99%
“…Made to order metal 3D printed devices (Hsu and Ellington 2015), 3D printed models for surgical planning (Pietrabissa et al 2015; Scawn et al 2015), and 3D printed tools (Burleson et al 2015) highlight some of the current and future biomedical applications of conventional 3D printing technologies. Bioprinting techniques have also been applied to bone tissue engineering.…”
Section: Applications Of Bioprintingmentioning
confidence: 99%
“…The printing material was the clear-PLA, which had been evaluated in previous other studies as a bolus material [23]. The bolus structure for printing was generated automatically above the body structure following the shape of the patient’s skin in the TPS.…”
Section: Discussionmentioning
confidence: 99%
“…The bolus substance must be odorless, non-sticky, and harmless to the skin. In this study, thus, the polylactic acid (PLA) was adopted as a bolus material [16, 17]. We printed a patient-specific breast bolus for an anthropomorphic phantom and simulated a real patient treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have confirmed the advantages of electron conformal therapy performed using customized 3D-printed electron boluses and compensators over that performed with conventional ones [7, 8, 11, 12]. However, since these studies used the 3D-printed boluses only on phantoms and did not provide details of the procedures used, there remained a lack of information regarding their use with actual patients.…”
Section: Methodsmentioning
confidence: 99%